Educação do campo – processo avaliativo em classe multisseriada em uma escola na Agrovila São Raimundo do município de Castanhal. - SANTOS, Joyce Damasceno (2018)
In fact the schools of the field, is the common teaching in multigrade classes happen, which we refer to the classrooms with students of different age range and education levels with a single teacher. In terms of howevaluation process is implemented ineducational system,objective of this study was to bring in his proposal an analysis on how to give the evaluation process in multisseriate class. The research is based through Caldart (2009), Hage (2005), Santos and Moura (2010), Freire (2005), Araújo and Guarnieri (2010), Luckesi (1992, 2011) Perrenoud (1999). The research is a qualitative approach, using as methodological approach the case study, observation and semi-structured interviews to collect data. Although the existential conditions and some difficulties are identified within the multisseriate schools, the results indicate that the evaluation process in multigrade develop equally to any other type of education, this perspective should be discarded negative views that arouse principle before experience the reality of these classes.